2011
DOI: 10.1186/1756-0500-4-326
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of methicillin resistant Staphylococcus aureus in the surgical units of Mulago hospital in Kampala, Uganda

Abstract: BackgroundThere is limited data on Methicillin resistant Staphylococcus aureus (MRSA) in Uganda where, as in most low income countries, the routine use of chromogenic agar for MRSA detection is not affordable. We aimed to determine MRSA prevalence among patients, healthcare workers (HCW) and the environment in the burns units at Mulago hospital, and compare the performance of CHROMagar with oxacillin for detection of MRSA.ResultsOne hundred samples (from 25 patients; 36 HCW; and 39 from the environment, one sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
70
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 18 publications
11
70
6
Order By: Relevance
“…While SCC mec type V strains have been isolated from hospital settings in Uganda, none were Spa type t318 [22]. However, Spa type t645, the second most frequent type in our collection (20.6%), also common in Western Europe and the Middle East (http://spaserver.ridom.de), was found to be the most frequent type isolated from SSI at Mulago National referral hospital [22], supporting the notion that there is a changing epidemiology reflected by community associated SCC mec genotypes being now more associated with hospital infections as observed elsewhere [23, 45]. However, it is noteworthy that some spa types of PVL+ S. aureus in the present study (t186, t729 and t355) have been previously identified in studies from Africa, and they all share the MLST type ST88 [46].…”
Section: Discussionsupporting
confidence: 82%
“…While SCC mec type V strains have been isolated from hospital settings in Uganda, none were Spa type t318 [22]. However, Spa type t645, the second most frequent type in our collection (20.6%), also common in Western Europe and the Middle East (http://spaserver.ridom.de), was found to be the most frequent type isolated from SSI at Mulago National referral hospital [22], supporting the notion that there is a changing epidemiology reflected by community associated SCC mec genotypes being now more associated with hospital infections as observed elsewhere [23, 45]. However, it is noteworthy that some spa types of PVL+ S. aureus in the present study (t186, t729 and t355) have been previously identified in studies from Africa, and they all share the MLST type ST88 [46].…”
Section: Discussionsupporting
confidence: 82%
“…The predominance of SCC mec type V was previously reported among isolates from the burns units at Mulago National Hospital [37] and in another study in Nigeria [34]. However, in these other studies SCC mec types I and III were also predominant.…”
Section: Discussionmentioning
confidence: 52%
“…This implies that the nasal carriage of Staphylococcus aureus in milkmen was 13% (4/31), lower than that reported in hospital settings in Uganda [22]. Additionally, similar species of CoNS to those detected in cows were identified; Staphylococcus scuiri (3), Staphylococcus saprophyticus (2), Staphylococcus xylosus (1) and Staphylococcus intermedius (1).…”
Section: Resultsmentioning
confidence: 82%